Soils: the final frontier recedes - Garbisu, Carlos; Alkorta, Itziar; Unamunzaga, Olatz (Frontiers in Soil Science, 2024)
Approximately 20 years ago (June 11th, 2004), a highly reputable scientific journal, on a front cover much celebrated by soil scientists, printed an eye-catching phrase: “Soils: The Final Frontier”. In the introduction to that special issue, it was mentioned that “in many ways the ground beneath our feet is as alien as a distant planet”, to then state that, owing to the booming interest in soil research at that time, together with the development of advanced techniques (e.g., next-generation sequencing), subterraneana would be made “seem far less of an alien experience”. In this perspective article, using as illustrations, by way of example only, two topics of great interest nowadays – soil carbon sequestration and soil biodiversity –, it is claimed that, despite all the efforts devoted in the last 20 years to the understanding of the soil ecosystem, the “final frontier” appears to have receded, as we are discovering increasing levels of complexity that are slowing down our trip to the far reaches of the edaphic universe. Due to, among other features, its high structural and functional complexity, biodiversity, heterogeneity, opacity, and processual and dynamic nature, the soil still remains a great unknown (“a black box”). The ultimate goal of this perspective article is to draw attention to the need for further long-term investment in research into this highly complex and fascinating ecosystem.